Graphene/ chitosan tubes inoculated with dental pulp stem cells promotes repair of facial nerve injury - Sun, Jingxuan; He, Lina; An, Qi; Ye, Xu; Ma, Jinjie; Yan, Jing; Xie, Xiaoqi; Sun, Xiangyu; Niu, Yumei; Cao, Wenxin (Frontiers in Chemistry, 2024)
Facial nerve injury significantly impacts both the physical and psychological well-being of patients. Despite advancements, there are still limitations associated with autografts transplantation.Consequently, there is an urgent need for effective artificial grafts to address these limitations and repair injuries. Recent years have witnessed the recognition of the beneficial effects of chitosan (CS) and graphene in the realm of nerve repair. Dental pulp stem cells (DPSCs) hold great promise due to their high proliferative and multi-directional differentiation capabilities. This study employed DPSCs as seed cells and a graphene/CS tube (G/CST) as a scaffold to investigate their combined effect on promoting facial nerve injury repair. Results indicate that G/CST possesses favorable physical and chemical properties, along with good cyto-compatibility, making it suitable for repairing facial nerve transection injuries. Furthermore, the synergistic application of G/CST and DPSCs significantly enhanced the repair process for a 10 mm facial nerve defect in rabbits, highlighting the efficacy of graphene as a reinforcement material and DPSCs as a functional material in facial nerve injury repair. This approach offers an effective treatment strategy and introduces a novel concept for clinically managing facial nerve injuries.